OPTIMIZATION OF PRODUCTIVE WAQF FOR IMPROVING COMMUNITY ECONOMIC WELFARE - Asra, Asra; Savitri, Asmah (University Muhammadiyah Aceh, 2023)
Indonesia is one of the largest Muslim countries in the world with a Muslim of more than 80% population. The awareness of the Indonesian people in carrying out social activities is very high, including waqf. Waqf is Islamic philanthropy which has long-term benefits. Many people carry out waqf because people believe waqf will make a big contribution to society, both for improving the quality of education, health and improving economic welfare. Nowadays, many waqfs are managed only to be used for cemeteries, mosques, schools and Islamic boarding schools, even though waqfs can not only be managed consumptively but can also be increased through productive waqf management so can provide sustainable benefits for the waqif and the community. Productive waqf management needs to be optimized so that waqf assets will increase and have more potential than before. In optimizing the productive empowerment of waqf assets, it is necessary to increase the role of professional nadzhir as equipped managers of waqf assets, government regulations also important role in increasing productive waqf and it is necessary to provide outreach to the community regarding the management and development of waqf assets through productive waqf.Keywords: Productive Waqf; Welfare and Community Economy.